Design of Second-Order Sliding Mode Guidance Law Based on the Nonhomogeneous Disturbance Observer - Huibo Zhou; Shenmin Song; Junhong Song; Jing Niu (Journal of Control Science and Engineering)
Considering the guidance problem of relative motion of missile target without the dynamic characteristics of missile autopilot in the interception planar, non-homogeneous disturbance observer is applied for finite-time estimation with respect to the target maneuvering affecting the guidance performance. Two guidance laws with finite-time convergence are designed by using a fast power rate reaching law and the prescribed sliding variable dynamics. The nonsingular terminal sliding mode surface is selected to improve dynamic characteristics of missile autopilot. Furthermore, the finite-time guidance law with dynamic delay characteristics is designed for the target maneuvering through adopting variable structure dynamic compensation. The simulation results demonstrate that, for different target maneuvering, the proposed guidance laws can restrain the sliding mode chattering problem effectively and make the missile hit the maneuvering target quickly and accurately with condition of corresponding assumptions.